Leaning final assembly : Increasing case company’s production volume by leaning - Kormano, Aki (My University, 2021)
Development and striving for better is important for every company. As competition intensifies, production must be constantly more efficient and more profitable. Creating value for the customer has become one of the most important things in the business world due to fierce competition. Lean thinking has emerged as one of the most significant topics of discussion in streamlining production and cutting costs. The simplicity of thought and common sense is combined in the word "waste". Waste means work or a stage in a process that does not add value and can be streamlined to reduce the efficiency of processes. Continuous development is also one of the key themes of lean thinking. The purpose of the work is to develop the final assembly of the client company so that it is possible to increase the production volume despite space constraints. The aim of the work is to find solutions to improve the flow, increase the number of assembly cells, minimize wastes, as well as working methods and even the working culture of the final assembly. The work also emphasizes more efficient use of existing resources. The research problem for this work has been selected as “How to improve productivity and increase production volume from existing facilities?” and the help questions have been chosen "what are the losses and how to reduce them?" and “how can lean thinking be used to develop production?” The theoretical basis of the work for development is Lean thinking. It has found theoretical and practical ways of working and development ideas that can be used to improve the volume of production now and in the future. In the factory, the final assembly acts as a bottleneck. Value stream mapping has been able to find many steps that can be removed or moved out of the final assembly to streamline the process.

Kehittyminen ja parempaan pyrkiminen on tärkeää jokaiselle yritykselle. Tuotannon tulee olla jatkuvasti tehokkaampaa ja kannattavampaa kilpailun kiristyessä. Arvon tuottaminen asiakkaalle on noussut keskiöön yritysmaailmassa kilpailun kiristyessä. Lean ajattelu on noussut yhdeksi keskeisimmistä keskustelun aiheista tuotantoa tehostaessa ja kustannuksia karsiessa. Ajatusmallin yksinkertaisuus ja maan läheisyys kiteytyy sanassa ”hukka” eli arvoa tuottamaton työ, jota karsimalla voidaan tehostaa työskentelyä. Myös jatkuva kehittäminen on yksi lean ajattelun keskeisistä teemoista. Työn tarkoituksena on kehittää toimeksiantajayrityksen loppukokoonpanoa siten, että tuotantovolyymia on mahdollista nostaa tilarajoitteista huolimatta. Tavoitteena työssä on löytää ratkaisuja virtaavuuden parantamiseen, työpisteiden lisäämiseen, erilaisien hukkien minimointiin sekä työtapoihin ja jopa loppukokoonpanon työskentelykulttuuriin. Tässä työssä painotetaan myös olemassa olevien resurssien tehokkaampaa hyödyntämistä. Tutkimusongelmaksi tähän työhön on valikoitunut “Kuinka parantaa tuottavuutta ja kasvattaa tuotantovolyymia nykyisistä tiloista?” Apukysymyksiksi on valittu siitä mitä ovat hukat ja kuinka vähentää niitä sekä kuinka lean ajattelun avulla voidaan kehittää tuotantoa. Työn teoreettisena pohjana kehitykselle on Lean ajattelu. Sen avulla on löydetty teoreettisia sekä käytännönläheisiä toimintatapoja ja kehitysideoita, joiden avulla tuotannon volyymia voidaan parantaa nyt ja myös tulevaisuudessa. Työssä on pystytty arvovirta kartoituksen avulla löytämään monia vaiheita, jotka on mahdollista poistaa kokonaan tai siirtää pois loppukokoonpanosta, joka toimii tehtaan pullonkaulana.
Keywords: lean manufacturing; development (active); efficiency (properties); product development; production planning; leadership (activity); leanness; productivity; wastes; production control; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management